Zimbabwe, Zambia, Malawi and Tanzania : Priority Fruit Species and Products for Tree Domestication and Commercialisation - Ham, Cori (World Bank, Washington, DC, 2012)
In collaboration with partners, the World Agro-forestry Centre established a number of fruit processing groups in Zimbabwe, Zambia, Malawi and Tanzania. These groups are actively involved in the processing of products such as wines and jams and sell their products in their respective districts. During 2003 a number of these groups and other stakeholders were consulted regarding the fruit species and products that they prefer to process, and other aspects such as training, marketing and general constraints. A total of 97 people attended three workshops at Magomero in Malawi, Tabora in Tanzania and Harare in Zimbabwe. The three workshops highlighted the differences in perceptions regarding fruit trees and fruit products between commercial and community processors, as well as between processors in different areas of southern Africa. Evidently, communities involved with the processing of fruit, prefer to utilize both indigenous and exotic species. In developing agro-forestry strategies it would be critical to consider these differences between processing groups. The focus should be on a range of tailor-made domestication and commercialization strategies for different processing groups, levels of commercial development and geographic regions. Such a strategy could present regional development agencies an opportunity to concentrate on smaller more focused projects instead of large regional initiatives that are difficult to manage.